Avtorskopravni vidiki plagiata s poudarkom na pisanih znanstvenih delih - Trampuž, Miha (Podjetje in delo, 2013)
In the introduction the author first deals with the broader general notion of plagiarism, then its legal notion and finally its narrower notion under copyright law. The latter is not defined in the Copyright Act, so that its subsumption under a legal notion, that does not exist and which is diversely defined in doctrine, is superfluous. Therefore dealing with it within copyright law is unnecessary, except de lege ferenda or concerning its contact points with the (broader) field of the scientific plagiarism. The first characteristic to be dealt with primarily is which intellectual content is protected against plagiarism. The author divides them into three groups and treats them accordingly (copyrighted content, broader protected content, non-protected content), whereby within the first group ideas, scientific theories and discoveries are expressly excluded from protection. The remaining three characteristics of plagiarism are the unauthorized factual use of the content, the appropriation of somebody elses authorship and a specific liability (intent). The article concludes with special cases of exclusion of plagiarism, i.e. selfquotations, double creations, unconscious taking of others works, inspiration and parody.
Keywords: avtorske pravice; avtorsko pravo; intelektualna lastnina; plagiatorstvo; znanstvenoraziskovalno delo